2008
DOI: 10.1021/jp0759574
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Study of Ce@C82:  Explanation of the Ce Preferential Bonding Site

Abstract: Ce has been found experimentally to be preferentially incorporated into the C82 isomer of C2v symmetry as have other lanthanoids in M@C82 (M = La, Pr, Nd, etc.). We have investigated the underlying reason for this preference by calculating structural and electronic properties of Ce@C82 using density functional theory. The ground-state structure of Ce@C82 is found to have the cerium atom attached to the six-membered ring on the C2 axis of the C82-C2v cage, and the encapsulated atom is found to perturb the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 59 publications
2
65
0
Order By: Relevance
“…[14][15][16] Prior studies of Ce@C 2v (9)-C 82 have not uncovered any evidenceo fd imerization of this molecule. [28] Ther esultsp resented herein on the SOMO spin density and pyramidalization (see Ta bleS 3i nt he Supporting Information) show very similar results for Ce@C 2v (9)-C 82 and La@C 2v (9)-C 82 .C onsequently,i ti sq uite re- markable to see such as triking differencei nt he formation of ad imer for Ce@C 2v (9)-C 82 and am onomer for La@C 2v (9)-C 82 after co-crystallization with Ni(OEP). [11,23,24] Previous computational studies have not suggested any unusual features in the electronic structure of monomeric Ce@C 2v (9)-C 82 that would cause dimerization.…”
Section: Dimerization Of Ce@c 2v (9)-c 82mentioning
confidence: 99%
“…[14][15][16] Prior studies of Ce@C 2v (9)-C 82 have not uncovered any evidenceo fd imerization of this molecule. [28] Ther esultsp resented herein on the SOMO spin density and pyramidalization (see Ta bleS 3i nt he Supporting Information) show very similar results for Ce@C 2v (9)-C 82 and La@C 2v (9)-C 82 .C onsequently,i ti sq uite re- markable to see such as triking differencei nt he formation of ad imer for Ce@C 2v (9)-C 82 and am onomer for La@C 2v (9)-C 82 after co-crystallization with Ni(OEP). [11,23,24] Previous computational studies have not suggested any unusual features in the electronic structure of monomeric Ce@C 2v (9)-C 82 that would cause dimerization.…”
Section: Dimerization Of Ce@c 2v (9)-c 82mentioning
confidence: 99%
“…DFT calculations of vibrational spectra of M@C 82 endohedral fullerenes were performed by several groups; [186][187][188][189] vibrational density of states were also calculated by Kemner and Zerbetto with the use of molecular dynamics calculations. 190 Kobayashi and Nagase reported B3LYP vibrational calculations for La@C 82 based on C 2v (9) cage isomer, 188 which afforded the frequencies of 159 cm −1 for a displacement along C 2 axis (A 1 symmetry type, "longitudal" mode) and 30 cm −1 and 27 cm −1 for two "latteral" modes (B 2 and B 1 symmetry, respectively), in reasonable agreement with experimental data.…”
Section: Vibrational Spectra Of Other Endohedral Fullerenesmentioning
confidence: 99%
“…Thus, it is very important to explore the structural, electronic, and vibrational properties of the fullerene C 20 and its endohedral metallofullerene. Additionally, previous studies have reported both experimentally and theoretically that the endohedral metallofullerenes containing Ce and Gd atoms may produce some novel physical and chemical properties [40][41][42][43][44][45][46][47][48][49][50][51][52] such as electrical conductance, magnetism, transport behavior, and nonlinear optical properties, etc. Moreover, the optical transition occurring due to the crystal field effect of the cage on the unfilled f orbitals of these atoms leads to the possibility of producing lasers out of metallofullerenes; and the conductivity of the solid metallofullerenes depends upon the electron donor capacity of the encapsulated atom.…”
Section: Introductionmentioning
confidence: 99%